Dynamic Mechanisms Associated With High-Energy Electron Flux Dropout in the Earth's Outer Radiation Belt Under the Influence of a Coronal Mass Ejection Sheath Region - Da Silva, L. A.; Shi, J.; Alves, L. R.; Sibeck, D.; Souza, V. M.; Marchezi, J. P.; Medeiros, C.; Vieira, L. E.A.; Agapitov, O.; Jauer, P. R.; Alves, M. E.S. [UNESP]; Wang, C.; et al. (American Geophysical Union (AGU), 2021)
The near-Earth interplanetary environment conditions affect the dynamics of the relativistic electron population quasitrapped in the radiation belts. A complex chain of processes observed in the magnetosphere can contribute to the variability of these populations when interplanetary structures, such as the interplanetary counterpart of a solar coronal mass ejection (ICME), and high-speed solar wind streams interact with the magnetosphere. However, as these processes can coexist, it is hard to untangle the relative contribution of each process to the loss of particles and the eventual repopulation. Here we show evidence that it is possible to distinguish the relative contribution of mechanisms related to the loss of the outer radiation belt electrons for an event observed on July 19 and 20, 2016. The interaction of an ICME's turbulent sheath with the Earth's magnetosphere resulted in a decrease in the outer radiation belt relativistic electron population. The ultralow frequency (ULF) and chorus wave activities are detected in the outer radiation belt during the time when the Earth's magnetosphere is under the influence of the ICME's sheath region, as well as the ICME's magnetic cloud region, while the electromagnetic ion cyclotron (EMIC) waves in the outer belt are observed only during the sheath region. Dynamic mechanisms such as magnetopause shadowing, outward radial diffusion driven by ULF waves, pitch-angle scattering driven by both EMIC and chorus waves are quantitatively analyzed. Our results suggest that the structures of the ICMEs can trigger the drivers to generate the different dynamic mechanisms responsible for the radiation belt population variability.